Effect of new-style anterior and posterior vaginal wall repair combined with modified ischial spine fascia fixation on patients with pelvic organ prolapse and their postoperative quality of life - Wang, Gensheng; Zhou, Shengju; Wang, Shuhua; Xu, Dongdi; Wang, Dan; Xu, Hongling; Gao, Chuanlong; Li, Qing (Frontiers in Surgery, 2022)
Objective: To explore the effect of new-style anterior and posterior vaginal wall repair combined with modified ischial spine fascia fixation on the effect of patients with pelvic organ prolapse (POP) and the impact of postoperative quality of life. Methods: A total of 88 patients with POP and elective surgery admitted to Anqing Hospital affiliated to Anhui Medical University from March 2018 to March 2021 were retrospectively analyzed. According to their surgical methods, patients were divided into observation group (44 cases, all underwent new-style anterior and posterior vaginal wall repair combined with modified ischial spine fascia fixation [new-style APVR- modified ISFF]) and control group (44 cases, all underwent traditional anterior and posterior vaginal wall repair combined with sacrospinous ligament fixation [traditional APVR- SLF]). The perioperative indicators were compared between the two groups. The pelvic floor function, pelvic organ prolapse quantification (POP-Q) classification and quality of life were observed before operation, 3 months after operation, and 6 months after operation. All patients were followed up. Results: Compared with the control group, the observation group had more advantages in intraoperative blood loss, operation time, urinary catheter indwelling time, postoperative anal exhaust time and hospitalization time (P<0.05). In terms of pelvic floor function, both groups of patients were significantly improved at 3 months and 6 months after surgery (P<0.05). In terms of quality of life, the two groups improved significantly at 6 months after surgery (P<0.05). The PFIQ-7, PFDI-20 and UDI-6P in observational group were lower than those of control group, while PISQ-12 was higher than control group, but all with no significant difference (P>0.005). In addition, the total complication rate of the observation group was 2.27% (1/44), which was significantly lower than that of the control group 22.73% (10/44) (P＜0.05). Conclusion: New-style APVR- modified ISFF can effectively treat POP and improve the quality of life of such patients, with low postoperative complications and high safety.